2017
DOI: 10.1186/s12906-017-1556-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allodynic effect of Buja in a rat model of oxaliplatin-induced peripheral neuropathy via spinal astrocytes and pro-inflammatory cytokines suppression

Abstract: BackgroundOxaliplatin, a widely used anticancer drug against metastatic colorectal cancer, can induce acute peripheral neuropathy, which is characterized by cold and mechanical allodynia. Activation of glial cells (e.g. astrocytes and microglia) and increase of pro-inflammatory cytokines (e.g. IL-1β and TNF-α) in the spinal cord play a crucial role in the pathogenesis of neuropathic pain. Our previous study demonstrated that Gyejigachulbu-Tang (GBT), a herbal complex formula, alleviates oxaliplatin-induced neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…Studies also showed that proinflammatory cytokines such as IL-6 play a critical role in STAT3 activation, 24 and oxaliplatin treatment significantly increased proinflammatory cytokines expression in the spinal cord. 25 In this study, we observed that the expressions of p-STAT3, cytokine TNF-α, and IL-1β were persistently upregulated in the DRG following oxaliplatin treatment. It is well known that IL-6-mediated STAT3 activation contributes to chronic inflammatory diseases, autoimmunity, and cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Studies also showed that proinflammatory cytokines such as IL-6 play a critical role in STAT3 activation, 24 and oxaliplatin treatment significantly increased proinflammatory cytokines expression in the spinal cord. 25 In this study, we observed that the expressions of p-STAT3, cytokine TNF-α, and IL-1β were persistently upregulated in the DRG following oxaliplatin treatment. It is well known that IL-6-mediated STAT3 activation contributes to chronic inflammatory diseases, autoimmunity, and cancer.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, the observed part also differed from paper to paper, as three studies focused on the DRG [22][23][24], whereas the rest analyzed the change in the spinal cord and the brain. Moreover, three studies observed the acute effect of oxaliplatin [18][19][20], whereas the rest assessed its chronic effect. In this review, we only included studies that conducted in vivo experiments along with glial assessment to better understand the change of glial activation in relation to different states of pain.…”
Section: Discussionmentioning
confidence: 99%
“…It also prevented the increase in the number of GFAP-positive cells. Jung et al [20] also showed that GFAP-positive cells increased after oxaliplatin administration and that oral administration of Buja (300 mg/kg) significantly decreased the upregulated GFAP-positive cell numbers. In the study by Makker et al [33], although consecutive injection of oxaliplatin significantly induced reduction in paw thresholds on D8, D13, and D16 in C57BL/6J mice, the astrocytic number in the spinal dorsal horn remained unchanged.…”
Section: Astrocytesmentioning
confidence: 95%
See 2 more Smart Citations